2023
DOI: 10.3390/d15091016
|View full text |Cite
|
Sign up to set email alerts
|

Next Generation Sequencing of Bee Gut Microbiota in Urban and Rural Environments

Mustafa Rüstemoğlu

Abstract: The gut microbiota plays a vital role in the physiological and behavioral processes of organisms, thereby influencing the quality of life of their host. Investigating the microbial diversity of the gut microbiota of Apis mellifera, the ecological organizer, may provide key insights into the ecological and health-related factors affecting host populations. This study aims to investigate the comparative gut microbiota of forager A. mellifera collected from both rural and urban environments in each of the four pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 90 publications
(141 reference statements)
0
1
0
Order By: Relevance
“…Recent research has shown that bee microbiome plays a critical role in determining the health status of both social and solitary bees ( Lozo et al., 2015 ; Engel et al., 2016 ; McFrederick and Rehan, 2016 ; Kwong et al., 2017 ). In addition, the choice of habitat location of honeybees may affect the core gut microbiome; human pathogens were detected in the gut of honeybee ( Rüstemoğlu, 2023 ). The benefits of fungal symbionts in honeybees include aiding in pollen degradation and assisting in the maturation of royal jelly; additionally, fungi may also serve as food sources ( Yun et al., 2018 ; de Paula et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown that bee microbiome plays a critical role in determining the health status of both social and solitary bees ( Lozo et al., 2015 ; Engel et al., 2016 ; McFrederick and Rehan, 2016 ; Kwong et al., 2017 ). In addition, the choice of habitat location of honeybees may affect the core gut microbiome; human pathogens were detected in the gut of honeybee ( Rüstemoğlu, 2023 ). The benefits of fungal symbionts in honeybees include aiding in pollen degradation and assisting in the maturation of royal jelly; additionally, fungi may also serve as food sources ( Yun et al., 2018 ; de Paula et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%